Accelerated aging of biochars: Impact on anion exchange capacity. (July 2016) - Lawrinenko, Michael; Laird, David A.; Johnson, Robert L.; Jing, Dapeng
Abstract: Little is known about the stability of biochar anion exchange capacity (AEC) and by what mechanisms AEC changes as biochar ages and weathers in soil environments. The goal of this study was to investigate chemical changes that may occur during ageing of biochar in neutral or alkaline soils and to assess the impact of ageing on AEC. To simulate and accelerate ageing, biochars were oxidized in alkaline hydrogen peroxide for 4 months. Spectroscopic evidence ( FTIR, XPS and 13 C-NMR ) revealed that ageing increased carbonyl and alcoholic character in biochars produced at 500 °C and effected endoperoxide formation in biochars produced at 700 °C; the latter exhibited greater arene carbon character. Ageing caused biochar AEC to decline on average by 54% with greater decreases in biochars produced at 500 °C in contrast to biochars produced at 700 °C. The AEC of biochar derived from alfalfa meal and cellulose produced at 700 °C did not change significantly (p = 0.20 and p = 0.50, respectively) with ageing. Stability of AEC in the high temperature biochars is attributed to the presence of oxonium groups in bridging positions of arene carbon, which are sterically resistant to nucleophilic attack.